Start Time and Worker Compensation: Implications for Staggered-Hours Programs - Eva Gutierrez-i-Puigarnau; Jos N. van Ommeren (Tinbergen Institute, 2010)
There is little known about the effects of staggered-hours programs that affect workers' working schedules to mitigate peak congestion. We examine the effect of workers' morning start times on their wages for Germany. In contrast to previous work based on cross-section data, we demonstrate that wages are not, or maybe, a slight inverse U-shaped function of start time suggesting that staggered-hours programs might be welfare enhancing.This discussion paper will result in a publication in 'Journal of Transport Economics and Policy' in 2012.
Keywords: R48; 330; Commuting; start time; wages; staggered hours; peak congestion; Arbeitszeitgestaltung; Arbeitsproduktivität; Lohnniveau; Bottleneck; Deutschland